Insights from Traditional and Geometric Morphometric Analyses of Selected Apis mellifera ruttneri Colonies in Gozo and Malta - Farrugia, Dylan (Journal of Apicultural Science, 2025)
The Maltese Islands host an endemic honey bee subspecies, Apis mellifera ruttneri . However, apiculture based on the imported foreign subspecies and strains greatly threatens the native A. m. ruttneri ’s status through hybridisation. This study examined the morphometric attributes of selected A. m. ruttneri colonies (n=34) on Gozo, following several years of operation of a commercial queen rearing enterprise using foreign subspecies and strains. Additionally, colonies of A. m. ruttneri (n=21) from neighbouring Malta were also examined, where the importation of foreign honey bee colonies has been ongoing for a significantly longer time. Sampling was carried out between August and November 2021. Traditional and geometric morphometry were used for wing analysis, with separate discriminant analysis classification models applied to each approach. Results revealed clear hybridisation trends in both Gozitan and Maltese sub-populations of A. m. ruttneri . These findings align with and echo concerns regarding local honey bee decline. This study underscores the urgent need for more decisive and concrete actions to holistically protect the Maltese honey bee and its vital role in local apiculture.